Terminology Development through Translanguaging as an Intellectualisation Strategy for African Languages in Andragogic Contexts - Nhongo, Raphael (Journal of Languages and Language Teaching, 2024)
Terminology has been identified as one of the impediments towards the intellectualisation and the subsequent use of African languages as languages of teaching and learning in specialised fields of knowledge. Although some terminologies have so far been compiled for specialised fields of knowledge, they seem not to be receiving acceptance in the functional spaces particularly the andragogic and pedagogic contexts. The central argument of the paper is that terminology needs to be created through the use of African languages in the process of teaching and learning in andragogic spaces instead of creating them through intuition, translation or knowledge of language. The communicative theory of terminology is used in the paper to argue for the adoption of specialised subject fields terminologies that are created in functional spaces. A sample of terms selected from isiNdebele and isiZulu that have so far been created for use in physics were used to critique the strategies that were adopted in their compilation. Terms for use in teaching and learning need not to be prescribed to the users but they should be harvested from functional academic spaces and then compiled for the writing of books and use in the classroom. A systematic way where the end users are involved in the process of term creation for specialised subject fields needs to be adopted.